Ireland : Financial Sector Assessment Program-Technical Note on Banking Supervision. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2022)
Supervision of less significant institutions (LSIs) is largely effective in Ireland. The Central Bank's supervisory approach to LSIs is intrusive and well-developed supervisory tools are appropriately applied. To enhance the capacity of supervisory tools and approaches, the supervision leverages on its membership in the Single Supervisory Mechanism (SSM). Supervision has sufficient rigor, although some gaps in the enforcement framework yet to be covered by the legislative changes planned for 2022.2 The supervisory responses to changing conditions are timely and agile. The expertise of supervisors is expanding with the development of the market, although keeping up its pace can be a challenge. The independence of banking supervision is strong in practice, and benefits from the safeguards of the SSM. Recent efforts to enhance cooperation between prudential and conduct supervision of banks (Central Bank's "One Bank" approach) has raised the quality of supervision, although scope remains for further enhancements to unleash the full potential of integrated prudential and conduct supervisory functions framed by strong cooperation arrangements and operational processes.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: International Agreements and Observance; International Organizations; Monetary Policy; Ireland